Community college leaders' perceptions of personal implementation of emotional intelligence (EI) skills - Mazeh, Yousra Y., author; Davies, Timothy, advisor; Banning, Jim, committee member; Kees, Nat, committee member; MacQuiddy, Susan, committee member (Colorado State University. Libraries, 2011)
According to American Association of Community Colleges (AACC), community college leaders who are able to master the skills that are related to organizational strategies, resource management, communication, collaboration, and professionalism, are most likely to succeed. According to Goleman (1998), acquiring these technical skills is important to achieve the job, yet a leader still needs other skills to become complete. In order to become effective leaders, according to Goleman, a person has to acquire the abilities which help him/her contribute positively to groups and institutions and sustain a balanced relationship with others on a daily basis. For Goleman (1995), in order for a leader to acquire the stated abilities, a leader has to implement emotional intelligence (EI) skills which include: showing responsibility, handling stress, being aware of self- emotions and those of others, being able to understand others, and are optimistic. This phenomenological study examined the reflections, values, challenges, and skills of community college leaders who try to promote leadership quality development using qualitative research methods to explore community college leaders lived experiences. The phenomenon in this study was examined through data collected by interviews with nine leaders who had at least 5 years of leadership at community colleges, and have a PhD in community college leadership. Many leaders demonstrated the need to create an environment where competition, disagreement, and conflict, could be resolved in a better way. Data analysis included the detailed data from participants and produced two emergent themes: EI skills are not yet fully understood enough to be implemented, and community college leaders rely on other varied approaches and skills.
Keywords: leadership; administration; community college; education; emotional intelligence; emotional intelligence leadership